Non-natriuretic peptide biomarkers in heart failure with preserved and reduced ejection fraction. (5th June 2018) - Oikonomou, Evangelos; Vogiatzi, Georgia; Tsalamandris, Sotiris; Mourouzis, Konstantinos; Siasos, Gerasimos; Lazaros, George; Skotsimara, Georgia; Marinos, George; Vavuranakis, Manolis; Tousoulis, Dimitris
Heart failure (HF) with reduced and preserved ejection fraction constitutes two entities with distinct pathogenetic backgrounds sharing common features. Beyond natriuretic peptides, several novel biomarkers have been proven useful in the diagnosis, prognosis and treatment of HF. Biomarkers of myocardial fibrosis have a low diagnostic yield in subjects with acute HF but may add prognostic information, especially in patients with HF and preserved ejection fraction. Biomarkers of renal impairment identify subjects with worse prognosis independently of left ventricle ejection fraction while inflammatory markers have not been proven useful in patients with systolic or diastolic impairment. In this review article, we summarize the main differences and application of non-natriuretic peptide biomarkers in HF patients with preserved and reduced ejection fraction.